The impact of sport engagement on life satisfaction, mental and psychological well-being among athletes - Özsari, A.; Uysal, H.; Lekesiz, G.; Çetin, M. Ç.; Tilki, M.; Gülgösteren, E.; Tek, T.; Altin, M. (PLOS ONE, 2026)
Physical inactivity is a prevalent issue worldwide with concerning implications for public health. Regular participation in sporting activities is associated with numerous physical, psychological, and social benefits. This research aimed to examine the the impact of sport engagement on sportive life satisfaction, mental well-being, and psychological well-being among 473 Turkish athletes, comprising 246 females and 227 males, from various sports disciplines: football, rugby, wrestling, kickboxing, archery, table tennis, taekwondo, volleyball, swimming, cycling, handball, and karate. Research data were collected through validated scales measuring sport engagement, sportive life satisfaction, mental well-being, and psychological well-being. In addition to descriptive statistics, hypotheses formulated within the research model were tested via correlation and multiple regression analyses within the relational model framework. Correlation analysis demonstrated a positive association between sport engagement and all three well-being dimensions. Multiple regression analyses further confirmed that sport engagement significantly and positively predicted sportive life satisfaction, mental and psychological well-being. Sports participation should be encouraged to enhance life satisfaction, mental and psychological well-being.